Preparation method and application of a high-quality single-unit-cell thick chromium-antimony magnetic film

The preparation of chromium-antimony magnetic films on strontium titanate substrates through molecular beam epitaxial growth technology has solved the problem of difficult control of the thickness of chromium-antimony films in the prior art, and achieved the preparation of high-quality single-cell thickness chromium-antimony magnetic films, which are suitable for new generation semiconductor devices.

CN119352146BActive Publication Date: 2025-04-11DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411932830.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high-quality single-cell thickness chromium-antimony magnetic films, and the layer thickness of the chromium-antimony film is difficult to control, which limits its application in new generation semiconductor devices.

Method used

Using molecular beam epitaxial growth technology, the chromium antimony magnetic film with high-quality single cell thickness was successfully prepared by evaporation of chromium and antimony sources on the strontium titanate substrate by controlling growth conditions such as temperature and beam flow ratio.

Benefits of technology

The preparation of a high-quality single-cell thickness chromium antimony magnetic film has been achieved. The film has a hexagonal lattice structure and significant magnetic anisotropy, good air stability, and a Curie temperature higher than room temperature, making it suitable for the new generation of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352146B_ABST
    Figure CN119352146B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a high-quality single-unit-cell thick chromium-antimony magnetic film, the method comprising: placing a strontium titanate substrate in the cavity of a molecular beam epitaxial growth device, degassing and high-temperature annealing the substrate under ultra-vacuum conditions until regular steps appear on the surface of the strontium titanate substrate; using a chromium source and an antimony source as evaporation sources, and using a molecular beam epitaxial growth technique to grow a chromium-antimony magnetic film on the pretreated substrate. The film prepared by the present invention has extremely significant magnetic anisotropy, its easy magnetization axis is along the out-of-plane direction, and the difference in magnetization intensity between the in-plane and out-of-plane directions is obvious; in addition, the film has ferromagnetism, and the coercive field gradually decreases with increasing temperature; in addition, the film also has stable magnetic properties, showing the characteristic that the Curie temperature is higher than room temperature. At the same time, the preparation method has the advantages of accurately controlling the number of film layers and high-quality growth, providing an ideal magnetic film material for the development of a new generation of semiconductor devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic materials, and more specifically, to a preparation method and application of a high-quality single-unit-cell thick chromium-antimony magnetic film. Background Art

[0002] In recent years, the discovery of two-dimensional ferromagnetic materials has attracted widespread attention and has great application prospects in data storage, sensors, high-performance spin-based computers and other nanodevices. A large number of theoretical and experimental studies are devoted to achieving long-range ferromagnetic order in two-dimensional materials that are stable at room temperature. Although the ferromagnetism of many two-dimensional materials has been confirmed, their Curie temperatures are often lower than room temperature and they are usually not air-stable, which severely limits their practical applications.

[0003] As a typical ferromagnetic material, chromium antimony has a Curie temperature of up to 710 K, and has great potential for application in semiconductor devices, especially the new generation of electronic devices that use the properties of electron spin for regulation. With the development of miniaturization in the semiconductor industry, the integration of electronic components is increasing, and there is a demand for ultra-thin layers or even atomic-level high-quality thin film materials. At present, the preparation methods of chromium antimony mainly include self-fluxing method and magnetron sputtering technology. The bulk phase material of chromium antimony is a non-van der Waals material, and the chromium antimony block grown by the self-fluxing method is extremely difficult to peel off into a thin layer. The crystal quality of the chromium antimony film grown by magnetron sputtering technology is poor, the thickness is generally tens of nanometers to microns, and the number of layers is not easy to control. At present, the preparation methods of chromium antimony are difficult to achieve the preparation of high-quality chromium antimony films, which seriously affects the application of chromium antimony materials in semiconductor devices. Therefore, exploring the preparation method of high-quality chromium antimony films has become an urgent problem to be solved.

[0004] Compared with other growth methods, molecular beam epitaxy has outstanding advantages: first, the entire growth process is carried out under ultra-high vacuum, using extremely high-purity elemental materials, which effectively avoids the interference of impurities, so extremely high-purity epitaxial films can be obtained; second, the growth rate is low, so that atoms or molecules have enough time to migrate on their surface; the temperature fluctuation of the growth source does not exceed ±1°C, and the growth beam is extremely stable, so that layer-by-layer growth of atomic layer thickness can be achieved; in addition, the low growth temperature reduces the mutual diffusion of substrate atoms and deposited atoms at the interface, and a clear interface structure can be obtained.

[0005] So far, there has been no report on the research on the preparation of single-unit cell thick chromium antimony films using molecular beam epitaxy technology. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing and applying a high-quality chromium-antimony magnetic film with a single unit cell thickness. For the first time, the molecular beam epitaxial growth technology is used to prepare a high-quality chromium-antimony magnetic film with a single unit cell thickness, and the thickness of the chromium-antimony magnetic film is controllable, laying a foundation for the application of chromium-antimony materials in a new generation of semiconductor devices.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film comprises the following steps:

[0009] (1) After cleaning, the strontium titanate substrate is placed in the cavity of a molecular beam epitaxial growth device, and the strontium titanate substrate is degassed and high-temperature annealed under ultra-vacuum conditions until a step with a width of 50 nm to 200 nm appears on the surface of the strontium titanate substrate, thereby obtaining a pretreated substrate. Specifically, the strontium titanate substrate selected in the present invention has the advantages of controllable crystal surface quality, atomic-level flatness, and high lattice matching with the thin film to be prepared, and through high-temperature pretreatment of the strontium titanate substrate, orderly flat steps are formed on the surface of the substrate, which can be used as a template to achieve efficient and controllable epitaxial growth of high-quality magnetic thin films.

[0010] (2) Using a chromium source and an antimony source as evaporation sources, a chromium-antimony magnetic thin film is grown on the pretreated substrate by molecular beam epitaxial growth technology, wherein the evaporation temperature of the chromium source is 1200°C to 1300°C, the evaporation temperature of the antimony source is 380°C to 420°C, the temperature of the pretreated substrate is maintained at 300°C to 360°C, the growth rate is 0.034 layer / min to 0.04 layer / min, the growth time is 25min to 30min, and the thickness of a single unit cell is 0.8 nm; the chromium-antimony magnetic thin film has a hexagonal lattice structure.

[0011] Optionally, in step (2), the ratio of the chromium source beam current to the antimony source beam current is 1:(9-11); the chromium source beam current during the growth process is 24.1 min / layer-29.4 min / layer, and the antimony source beam current is 2.41 min / layer-2.94 min / layer. Specifically, by adjusting the growth parameters and the beam current ratio of Cr and Sb, the preparation of chromium-antimony magnetic films with different layer thicknesses can be achieved.

[0012] Optionally, in step (2), the evaporation temperature of the chromium source is 1240°C to 1260°C, the evaporation temperature of the antimony source is 390°C to 410°C, the temperature of the pretreated substrate is maintained at 320°C to 340°C, and the growth rate is 0.036 layer / min to 0.038 layer / min.

[0013] Optionally, the degassing and high temperature annealing in step (1) includes: -10mbar~1×10 -9 Under ultra-vacuum conditions of mbar, the strontium titanate substrate is heated to 380°C to 420°C and kept at this temperature for 1.5h to 2.5h for degassing, and then the substrate is heated to 800°C to 1000°C and kept at this temperature for 0.25h to 0.75h.

[0014] Optionally, the strontium titanate substrate in step (1) is a SrTiO3 (001) wafer or a SrTiO3 (111) wafer.

[0015] Optionally, in step (2), the heating rate of the substrate is 14°C / min~16°C / min; the heating rate of the chromium source is 28°C / min~32°C / min to ensure stable evaporation of chromium; the heating rate of the antimony source is 14°C / min~16°C / min to ensure stable evaporation of antimony; the vacuum is maintained at 5×10 -10 mbar~1×10 -9 mbar.

[0016] Optionally, in step (2), the heating rate of the substrate is 14.5°C / min~15.5°C / min; the heating rate of the chromium source is 29°C / min~31°C / min; the heating rate of the antimony source is 14.5°C / min~15.5°C / min

[0017] Optionally, the cleaning in step (1) includes: placing the strontium titanate substrate in anhydrous ethanol and ultrasonically cleaning it for 15 minutes. After cleaning, take it out with tweezers and gently wipe off excess ethanol with dust-free paper.

[0018] Optionally, in step (1), an infrared thermometer is used to monitor the degassing temperature and the annealing temperature; and a scanning tunneling microscope is used to observe the regular step structure on the surface of the pretreated substrate.

[0019] Optionally, in step (2), a scanning tunneling microscope image is used to measure the thickness of a single unit cell.

[0020] The invention also discloses a high-quality single-unit-cell-thickness chromium-antimony magnetic film prepared by the above-mentioned preparation method.

[0021] The present invention also discloses an application of a high-quality single-unit-cell thick chromium-antimony magnetic film prepared by the above-mentioned preparation method in a new generation of semiconductor devices.

[0022] Implementing the embodiments of the present invention will have the following beneficial effects:

[0023] (1) The preparation method provided by the present invention uses strontium titanate single crystal as a substrate, utilizes a chromium source and an antimony source as reaction materials, and for the first time utilizes molecular beam epitaxial growth technology in combination with an ultra-high vacuum environment and precise temperature control to successfully prepare a high-quality single-unit cell thick chromium antimony magnetic film. The entire growth process is carried out under ultra-high vacuum, using extremely high-purity elemental materials, effectively avoiding interference from impurities, and obtaining an extremely high-purity epitaxial film.

[0024] (2) The chromium antimony magnetic film prepared by the preparation method provided by the present invention exhibits extremely significant magnetic anisotropy, with its easy magnetization axis along the out-of-plane direction, and the difference in magnetization intensity between the in-plane and out-of-plane directions is obvious. The magnetic test of the film shows a clear hysteresis loop, indicating that the film is ferromagnetic, and the coercive field gradually decreases with increasing temperature. In addition, the film also has stable magnetic properties, good air stability, and exhibits the characteristic of a Curie temperature higher than room temperature. It is a room temperature two-dimensional magnet, which is conducive to the application of magnetic materials in new generation semiconductor devices.

[0025] (3) The molecular beam epitaxy equipment used in the present invention can realize layer-by-layer growth of atomic layer thickness, and can obtain chromium antimony magnetic films of different thicknesses.

[0026] (4) The preparation method of the present invention has the advantages of precise control of the number of thin film layers and high-quality growth, providing an ideal thin film material for the development of a new generation of semiconductor devices. It is expected to be applied to information storage, transmission and processing, and will play an important role in the post-Moore era.

[0027] In summary, the present invention selects a strontium titanate single crystal substrate, uses chromium and antimony as evaporation sources, combines substrate pretreatment and optimization of growth conditions, and successfully prepares a chromium-antimony magnetic film with a single unit cell thickness of 0.8 nm through molecular beam epitaxial growth technology. The film has a hexagonal lattice structure, which overcomes the problems in the prior art that the bulk chromium-antimony single crystal grown by the self-flux method is difficult to cleave and is difficult to peel into thin films, and the chromium-antimony film grown by magnetron sputtering technology has poor crystal quality and is difficult to control the number of layers. The new preparation process is expanded. The method for preparing a single unit cell high-quality chromium-antimony film by molecular beam epitaxial growth technology proposed in the present invention is precise and controllable, can achieve the characteristics of layer-by-layer growth of atomic layer thickness, and the number of film layers is controllable, which is conducive to the large-scale application of chromium-antimony thin film materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The controllable growth of thin films of different thicknesses according to the embodiment of the present invention is achieved by precisely controlling the evaporation temperature of the Cr source and the Sb source, the heating temperature of the substrate, and the growth time.

[0029] Figure 2This is the scanning tunneling microscopy spectrum of the first and second chromium antimony magnetic films of Test Example 1 of the present invention.

[0030] Figure 3 This is a scanning tunneling microscope (STM) image of the single-cell layer chromium antimony magnetic film of Test Example 1 of the present invention.

[0031] Figure 4 This is a magnetic susceptibility-magnetic field data diagram of a single-cell layer chromium-antimony magnetic film of Test Example 2 of the present invention; the magnetic field is along the out-of-plane direction.

[0032] Figure 5 This is a magnetic susceptibility-magnetic field data diagram of a single-cell layer chromium-antimony magnetic film of Test Example 2 of the present invention; the magnetic field is along the in-plane direction.

[0033] Figure 6 This is a coercive field-temperature data diagram of a single-cell layer chromium-antimony magnetic film of Test Example 2 of the present invention; the magnetic field is along the out-of-plane direction.

[0034] Figure 7 These are STM images of the chromium antimony magnetic films grown in Examples 1-5 of the present invention and Comparative Examples 1 and 2.

[0035] Figure 8 These are STM images of the chromium antimony magnetic films grown in Examples 1, 6-9 of the present invention and Comparative Examples 3 and 4. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0037] Example 1

[0038] The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film of this embodiment comprises the following steps:

[0039] (1) After cleaning, the strontium titanate substrate (SrTiO3 (001) or SrTiO3 (111)) was loaded into a sample holder and placed in the chamber of a molecular beam epitaxial growth device. Current was applied to the sample holder and the temperature of the substrate was measured using an infrared thermometer at 5×10 -10 mbar~1×10 -9 The strontium titanate substrate was heated to 400°C under ultra-vacuum conditions of 30 mbar and kept at this temperature for 2 hours for degassing. The substrate was then heated to 800°C and kept at this temperature for 0.5 hours for high-temperature annealing until steps with a width of 50 nm to 200 nm appeared on the surface of the strontium titanate substrate, thereby obtaining a pretreated substrate.

[0040] (2) Using chromium source and antimony source as evaporation sources, molecular beam epitaxial growth technology was used to grow chromium-antimony magnetic thin film on the pretreated substrate, wherein the chromium source was heated to 1250°C at a rate of 30°C / min, the antimony source was heated to 400°C at a rate of 15°C / min, the pretreated substrate was heated to 330°C at a rate of 15°C / min, the ratio of chromium source beam current to antimony source beam current was 1:10, the chromium source beam current during the growth process was 26.8 min / layer, the antimony source beam current was 2.68 min / layer, the growth rate was controlled to be 0.037 layer / min, the growth time was 27 min, and a single-layer chromium-antimony magnetic thin film was obtained.

[0041] Test Example 1

[0042] Scanning tunneling microscope test

[0043] The single-cell chromium antimony thin film material obtained in Example 1 was measured using a low-temperature scanning tunneling microscope (LT-STM) produced by German ScientaOmicron Company, and the test temperature range was 4.5 K to 77 K. Figure 1 As shown, the morphology and thickness of the film can be measured by scanning tunneling microscopy. By precisely controlling the evaporation temperature of the Cr source and Sb source, the heating temperature of the substrate, the growth rate, the growth time, the beam current ratio of the chromium source and the antimony source, and combining the substrate pretreatment, the controllable growth of films of different thicknesses is achieved, and the surface is flat. By controlling the thickness, the electronic state near the Fermi surface can be controlled. The scanning tunneling spectrum results show that a significant energy gap appears below the Fermi energy, and the state density near the Fermi surface gradually increases, revealing that the chromium antimony film exhibits electron-doped n-type semiconductor characteristics ( Figure 2 ). Compared with the first film, the dI / dV spectrum peak of the second CrSb film shifts to a higher binding energy, suggesting that electrons move from the second layer to the first layer and the substrate. Abnormal behavior near the Fermi surface was observed in the first film, which may be due to the Kondo effect. Figure 3 The film shows an ordered structure with a hexagonal lattice and a period of 0.782 nm.

[0044] Test Example 2

[0045] Magnetic susceptibility test

[0046] The magnetic susceptibility of the single-cell chromium-antimony thin film material obtained in Example 1 was tested using a comprehensive physical property measurement system (PPMS) produced by Quantumdesign, USA. The test temperature range was 2-300 K and the maximum magnetic field was 9 T. The magnetic susceptibility measurement results show that the magnetic anisotropy of the single-layer chromium-antimony film in the plane and out of the plane is very significant ( Figure 4 and Figure 5), the magnetization intensity in the out-of-plane and in-plane directions differs by two orders of magnitude, indicating that the easy magnetization axis is along the out-of-plane direction. The hysteresis loop shows that the film is ferromagnetic, and the temperature-dependent MH curve further shows that as the temperature increases, the coercive field decreases from 397 Oe to 198 Oe ( Figure 6 ).

[0047] Example 2

[0048] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the chromium source is 1200°C.

[0049] Example 3

[0050] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the chromium source is 1240°C.

[0051] Example 4

[0052] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the chromium source is 1260°C.

[0053] Example 5

[0054] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the chromium source is 1300°C.

[0055] Comparative Example 1

[0056] The only difference between this comparative example and Example 1 is that the evaporation temperature of the chromium source is 1050°C.

[0057] Comparative Example 2

[0058] The only difference between this comparative example and Example 1 is that the evaporation temperature of the chromium source is 1100°C.

[0059] Example 6

[0060] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the antimony source is 390°C.

[0061] Example 7

[0062] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the antimony source is 380°C.

[0063] Example 8

[0064] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the antimony source is 410°C.

[0065] Example 9

[0066] The only difference between this embodiment and embodiment 1 is that the evaporation temperature of the antimony source is 420°C.

[0067] Comparative Example 3

[0068] The only difference between this comparative example and Example 1 is that the evaporation temperature of the antimony source is 360°C.

[0069] Comparative Example 4

[0070] The only difference between this comparative example and Example 1 is that the evaporation temperature of the antimony source is 440°C.

[0071] The STM results of the chromium antimony magnetic films grown according to Examples 1-9 and Comparative Examples 1-4 are as follows: Figure 7 , as shown in 8. It can be seen that compared with comparative examples 1-4, the chromium-antimony magnetic films grown in embodiments 1-9 are significantly superior in step clarity and surface flatness. This shows that the optimized growth conditions in the embodiments can effectively improve the quality of the film and overcome the shortcomings in the comparative examples. In particular, in Example 1, the optimal growth conditions were achieved by precisely controlling the chromium source evaporation temperature at 1250°C and setting the antimony source evaporation temperature to 400°C. Under these conditions, the obtained chromium-antimony magnetic film not only has the most obvious step structure, but also has an extremely high surface flatness, which is better than other embodiments and comparative examples. These results fully prove that the process parameters of Example 1 are optimal, and provide a key reference for the preparation of high-quality chromium-antimony magnetic films.

[0072] Example 10

[0073] The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film of this embodiment comprises the following steps:

[0074] (1) After cleaning, the strontium titanate substrate (SrTiO3 (001) or SrTiO3 (111)) was loaded into a sample holder and placed in the chamber of a molecular beam epitaxial growth device. Current was applied to the sample holder and the temperature of the substrate was measured using an infrared thermometer at 5×10 -10 mbar~1×10 -9 The strontium titanate substrate was heated to 380°C under ultra-vacuum conditions of 1.3 mbar and kept at this temperature for 1.5 h for degassing. The substrate was then heated to 900°C and kept at this temperature for 0.55 h for high-temperature annealing until a step with a width of 50 nm to 200 nm appeared on the surface of the strontium titanate substrate, thereby obtaining a pretreated substrate.

[0075] (2) Using chromium source and antimony source as evaporation sources, molecular beam epitaxial growth technology was used to grow chromium-antimony magnetic thin film on the pretreated substrate, wherein the chromium source was heated to 1250°C at a rate of 29°C / min, the antimony source was heated to 400°C at a rate of 14.5°C / min, the pretreated substrate was heated to 320°C at a rate of 14.5°C / min, the ratio of chromium source beam current to antimony source beam current was 1:10, the chromium source beam current during the growth process was 24.1 min / layer, the antimony source beam current was 2.41 min / layer, the growth rate was controlled to be 0.036 layer / min, the growth time was 28 min, and a single-layer chromium-antimony magnetic thin film was obtained.

[0076] Embodiment 11

[0077] The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film of this embodiment comprises the following steps:

[0078] (1) After cleaning, the strontium titanate substrate (SrTiO3 (001) or SrTiO3 (111)) was loaded into a sample holder and placed in the chamber of a molecular beam epitaxial growth device. Current was applied to the sample holder and the temperature of the substrate was measured using an infrared thermometer at 5×10 -10 mbar~1×10 -9 The strontium titanate substrate was heated to 420°C under ultra-vacuum conditions of 100 mbar and kept at this temperature for 2.5 hours for degassing. The substrate was then heated to 1000°C and kept at this temperature for 0.5 hours for high-temperature annealing until a step with a width of 50 nm to 200 nm appeared on the surface of the strontium titanate substrate, thereby obtaining a pretreated substrate.

[0079] (2) Using chromium source and antimony source as evaporation sources, molecular beam epitaxial growth technology was used to grow chromium-antimony magnetic thin film on the pretreated substrate, wherein the chromium source was heated to 1250°C at a rate of 31°C / min, the antimony source was heated to 400°C at a rate of 15.5°C / min, the pretreated substrate was heated to 340°C at a rate of 15.5°C / min, the ratio of chromium source beam current to antimony source beam current was 1:10, the chromium source beam current during the growth process was 29.4 min / layer, the antimony source beam current was 2.94 min / layer, the growth rate was controlled to be 0.038 layer / min, the growth time was 24 min, and a single-layer chromium-antimony magnetic thin film was obtained.

[0080] The effects achieved by Example 10-Example 11 are the same as those achieved by Example 1.

[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a high-quality single-unit cell thick chromium-antimony magnetic film, characterized in that: The following steps are involved: (1) After cleaning, the strontium titanate substrate is placed in the chamber of a molecular beam epitaxial growth device, and the strontium titanate substrate is degassed and high-temperature annealed under ultra-vacuum conditions until a step with a width of 50 nm to 200 nm appears on the surface of the strontium titanate substrate, thereby obtaining a pretreated substrate; (2) Using a chromium source and an antimony source as evaporation sources, a chromium-antimony magnetic thin film is grown on the pretreated substrate by molecular beam epitaxial growth technology, wherein the evaporation temperature of the chromium source is 1240°C to 1260°C, the evaporation temperature of the antimony source is 390°C to 410°C, the temperature of the pretreated substrate is maintained at 320°C to 340°C, the growth rate is 0.036 layer / min to 0.038 layer / min, the growth time is 25min to 30min, and the thickness of a single unit cell is 0.8 nm; the chromium-antimony magnetic thin film has a hexagonal lattice structure.

2. The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film according to claim 1, characterized in that: In step (2), the ratio of the chromium source beam current to the antimony source beam current is 1:(9-11); during the growth process, the chromium source beam current is 24.1 min / layer-29.4 min / layer, and the antimony source beam current is 2.41 min / layer-2.94 min / layer.

3. The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film according to claim 1, characterized in that: The degassing and high temperature annealing in step (1) include: In 5×10 -10 mbar~1×10 -9 Under ultra-high vacuum conditions of 100 mbar, the strontium titanate substrate is heated to 380° C. to 420° C. and kept warm for 1.5 h to 2.5 h for degassing, and then the substrate is heated to 800° C. to 1000° C. and kept warm for 0.25 h to 0.75 h.

4. The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film according to claim 1, characterized in that: The strontium titanate substrate in step (1) is a SrTiO3 (001) wafer or a SrTiO3 (111) wafer.

5. The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film according to claim 1, characterized in that: In step (2), the heating rate of the substrate is 14°C / min~16°C / min; the heating rate of the chromium source is 28°C / min~32°C / min; the heating rate of the antimony source is 14°C / min~16°C / min; the vacuum is maintained at 5×10 -10 mbar~1×10 -9 mbar.

6. The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film according to claim 5, characterized in that: In step (2), the heating rate of the substrate is 14.5°C / min~15.5°C / min; the heating rate of the chromium source is 29°C / min~31°C / min; and the heating rate of the antimony source is 14.5°C / min~15.5°C / min.

7. The method for preparing a high-quality single-unit-cell thick chromium-antimony magnetic film according to claim 1, characterized in that: The cleaning in step (1) includes: placing the strontium titanate substrate in anhydrous ethanol, ultrasonically cleaning it for 15 minutes, and after cleaning, taking it out with tweezers and gently wiping off excess ethanol with dust-free paper.

8. A high-quality single-cell thick chromium-antimony magnetic film prepared by the preparation method as described in any one of claims 1 to 7.

9. Application of a high-quality single-unit-cell thick chromium-antimony magnetic film prepared by the preparation method as claimed in any one of claims 1 to 7 in a semiconductor device.

Citation Information

Patent Citations

  • Zinc blende type CrSb compound, method for fabricating the same, and multilayered structure

    US20030003704A1